Faktor Risiko yang Berhubungan dengan Kejadian Stunting pada Balita di Sulawesi Barat: Analisis Data SSGI 2024 - Jeanette Silvia Mataheru; Diah Mulyawati Utari (Malahayati Nursing Journal, 2026)
ABSTRACT Stunting is a chronic form of undernutrition with long-term consequences for children’s growth and development. Although the national prevalence of stunting in Indonesia has shown a downward trend, the rate in West Sulawesi Province remains high and exceeds the national average. This study aimed to examine risk factors associated with stunting among under-five children in West Sulawesi using data from the 2024 Indonesian Nutrition Status Survey (SSGI). A cross-sectional design with complex survey analysis was applied. Risk factors were assessed using bivariate and multivariate logistic regression and are presented as odds ratios (ORs) with 95% confidence intervals. The prevalence of stunting was 35.6%. Multivariate analysis identified low birth weight as the strongest risk factor for stunting (aOR = 2.08; 95% CI: 1.60–2.70). Other factors significantly associated with stunting included male sex (aOR = 1.24; 95% CI: 1.05–1.47), use of unprotected drinking water sources (aOR = 1.43; 95% CI: 1.08–1.90), low maternal education (aOR = 1.91; 95% CI: 1.45–2.51), medium maternal education (aOR = 1.36; 95% CI: 1.05–1.85), and maternal chronic energy deficiency during pregnancy (aOR = 1.47; 95% CI: 1.10–1.96). Stunting among children in West Sulawesi is influenced by a combination of biological, sociodemographic, and environmental factors, underscoring the need for integrated preventive interventions starting from pregnancy through early childhood. Keywords: Malnutrition, Stunting, Growth Dissorder, Toddler.  ABSTRAK Stunting merupakan masalah gizi kronis yang berdampak jangka panjang terhadap pertumbuhan dan perkembangan anak. Meskipun prevalensi stunting nasional cenderung menurun, Provinsi Sulawesi Barat masih menunjukkan angka yang tinggi lebih dari rata-rata nasional. Penelitian ini bertujuan menganalisis faktor risiko yang berhubungan dengan kejadian stunting pada balita di Provinsi Sulawesi Barat berdasarkan data Survei Status Gizi Indonesia (SSGI) tahun 2024. Penelitian ini menggunakan desain potong lintang dengan analisis survei kompleks. Faktor risiko dianalisis menggunakan regresi logistik bivariat dan multivariat, serta disajikan dalam odds ratio (OR) dan interval kepercayaan 95%. Prevalensi stunting pada balita sebesar 35,6%. Analisis multivariat menunjukkan bahwa berat badan lahir rendah (BBLR) merupakan faktor risiko paling kuat terhadap stunting (aOR = 2,08; 95% CI: 1,60–2,70). Faktor lain yang berhubungan signifikan adalah jenis kelamin laki-laki (aOR = 1,24; 95% CI: 1,05–1,47), akses sumber air minum tidak terlindungi (aOR = 1,43; 95% CI: 1,08–1,90), pendidikan ibu rendah (aOR = 1,91; 95% CI: 1,45–2,51), pendidikan ibu menengah (aOR = 1,36; 95% CI: 1,05–1,85), serta riwayat kekurangan energi kronik (KEK) pada ibu saat hamil (aOR = 1,47; 95% CI: 1,10–1,96). Stunting pada balita di Sulawesi Barat dipengaruhi oleh faktor biologis, sosiodemografis, dan lingkungan, sehingga pencegahan perlu dilakukan secara terintegrasi sejak masa kehamilan hingga awal kehidupan anak. Kata Kunci: Malnutrisi, Stunting, Gangguan Pertumbuhan, Balita.